Pengaruh Brand Image, User Image, dan Product Image terhadap Keputusan Pembelian Mobil Mitsubishi Pajero pada PT. Bosowa Berlian Motor di Kota Makassar - Misrayanti Saleh; Siti Haerani; Andi Reni (Hasanuddin Journal of Business Strategy, 2019)
Today, Consumers are very critical in buying, offering products that very much make consumers more selective in determining the choice of products to buy. This study aims to determine which brand image (brand image), user image (user image), and product image (product image) that most influence the decision to purchase a Mitsubishi Pajero car in Makassar City. The type of data used is qualitative data and quantitative data. The population in this study are all consumers of PT. Bosowa Berlian Motor bought a Mitsubishi Pajero car. The sample in this study has certain criteria as for these criteria, which are users of the Mitsubishi Pajero and the duration of use of at least 1 year. Data collection in this study uses a questionnaire. Data were analyzed using multiple linear regression analysis. The results of this study indicate that all brand image variables, user image, and product image of the decision to purchase a Mitsubishi Pajero car at Bosowa Berlian Motor in Makassar have a positive and significant influence on the decision dependent variable purchase of a Mitsubishi Pajero car at PT Bosowa Berlian Motor in Makassar. Product image (product image) is the most influential variable when compared to other variable data, namely brand image (brand image) and user image (user image).